Desenvolvimento de dispositivos descartáveis com tintas condutoras e substratos de baixo custo para sensoriamento e biossensoriamento de disfunções hormonais - Camargo, Jéssica Rocha (Universidade Federal de São Carlos, 2024)
Advances in new electrochemical sensor architectures that enable rapid analysis in miniaturized form and with high sensitivity are one of the most important areas of recent years. This importance is since electrochemical systems are easy to produce in the laboratory and can be developed even in emerging countries due to their relatively low cost. The materials used to produce conductive inks usually include a polymeric vehicle, a conductive material and possible additives that, in appropriate proportions, form an ink suitable for printing on an inert substrate. In this context, we present some proposals for sensors made with low-cost conductive inks. In Chapter 1, a new water-based conductive ink was developed for the fabrication of disposable screen-printed electrodes specifically intended for the detection of uric acid (UA) and catechol. The choice of a water-based ink offers advantages in terms of reduced toxicity and environmental impact. For UA, the linear range was between 8.0 and 500.0 µmol L−1and a limit of detection (LOD) of 3.63×10−7 mol L−1. The proposed CGG/PET is more flexible and cost-effective than commercial electrodes, with an estimated manufacturing price of only 0.006 dollars or 0.033 reais per electrode. For catechol, the linear range was between 0.5 and 50 µmol L−1, and a LOD of 0.3 µmol L−1. Chapter 2 focused on developing new silver ink compositions to prepare pseudo-reference electrodes, which are essential for many electrochemical applications. As a proof of concept for the silver inks, the detection of β- estradiol was performed. At β-estradiol concentrations in the linear range of 1.0 to 100 µmol L−1 and a LOD of 1.3 × 10−7 mol L−1, was obtained for the system referenced by the Ag-NP ink. For the system referred to by the Ag-SL ink, a LOD of 9.5 × 10−7 mol L−1. The cost was approximately US$ 2.02/R$ 11.06 per gram of ink with nail polish and US$ 2.40/R$ 13.14 per gram of ink with shellac. In Chapter 3, an electrochemical system using shellac, graphite and platinum was developed for the biosensor of estrone (E1), a steroid hormone that may be associated with diseases such as premature menopause, polycystic ovary syndrome and breast cancer. At E1 concentrations ranging from 5.0 to 1000 nmol L−1, with a LOD of 0.70 nmol L−1, the total cost was 0.79 reais per biosensor. Finally, in Chapter 4, screen-printed electrodes made of Super P carbon black, polyvinylpyrrolidone (PVP) and chitosan were discussed for the detection of tryptophan (TRP), an essential amino acid with various important biological functions. The linear range for TRP was 0.5 to 300 μmol L−1 with an LOD of 0.018 μmol L−1 and an LOQ of 0.060 μmol L−1. All inks developed in this thesis showed satisfactory results and are excellent alternatives for the development of disposable electrochemical systems. Thus, the developed inks and architectures are cost-effective and can be used for sensing and biosensing of various analytes and biomarkers related to diseases that directly affect human health.
Development of disposable devices with conductive inks and low-cost substrates for sensing and biosensing of hormonal dysfunctions
Keywords: Sensores eletroquímicos; Biossensores; Tintas condutoras; Eletrodos descartáveis; Electrochemical sensors; Electrochemical biosensors; Conductive inks; Disposable electrodes; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA